The Elusive Silver Lining: Caring for Patients in the HIV/AIDS "War Zone". How Did Nurses Sustain It? Bene t-Finding Analysis - Jacob, Carl GA; Lagacé-Roy, Daniel; Lussier-Duynstee, Patricia (Université d'Ottawa | University of Ottawa, 2022)
Using a review of literature consisting of peer-reviewed articles and grey literature, this paper presents a narrative and graphic representation of the key concepts underpinning the benefits nurses perceived deriving from caring for patients during the HIV/AIDS pandemic. Our review indicates that benefits were seldom the focus of the literature and were mostly integrated within documents pertaining to the negative aspects of caring for these patients. In such a context, this research identified self-enhancement benefits in three domains (work benefits, work attributes, and work ethos), and self-actualization benefits in three domains (relationships, transformation, and humanity). During the COVID-19 pandemic, researchers are once again enticed to write scientific literature about the impact of caring in a "war zone". Using the underpinning concepts identified through the benefit-finding research in the context of the HIV/AIDS pandemic, researchers could identify the many perceived benefits nurses derive from caring for infected patients during this pandemic.
Keywords: Education; Nurses; HIV/AIDS; Pandemic; Benefit Finding; Covid-19